Optical Double Binary Amplitude Mask Structure for Security Authentication - Xiaogang Wang; Guoquan Zhou; Chaoqing Dai (IEEE Photonics Journal)
A novel method for jointly designing two binary amplitude masks (BAMs) that allow for secure authentication is proposed. The speckle-noise diffraction pattern generated numerically from the input secret image encrypted by a random phase is binarized and further compressed. The resulting BAM can be separated into two desired BAMs, each of which does not visually render the primary information when applied for verification. Simulation results are presented to verify the validity and effectiveness of the proposed method.